Applying: To Derrida
XXV, 239 p.
Keywords: Striking out from a number of new headings and in a number of new directions each of the essays in this collection pushes at the borders of their topics, disciplines and ways of thinking, providing innovative and inventive insights into the work - and application - of Jacques Derrida on a diverse range of themes including Irish identity, communication, ethics, love, tele-technology, Victorian studies, the limits of philosophy, translation, otherness and literature, demonstrating that, today, despite repeated accusations over recent years that the work of Derrida has become passe, there is more vitality and spirit in engaging with the writings of Derrida than ever before.